2017
DOI: 10.1093/ajcp/aqx015
|View full text |Cite
|
Sign up to set email alerts
|

Massive Gastric Juvenile Polyposis

Abstract: SMAD4 immunohistochemstry is a helpful ancillary diagnostic test in cases of suspected juvenile polyposis syndrome involving the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, it is very difficult to accurately diagnose cancerous lesions among the numerous polyps present in cases of GJP coexisting with gastric cancer. Indeed, no case study has yet reported an accurate initial diagnosis of coexisting GJP and cancerous lesions with M-NBI and a target biopsy (Table) (15)(16)(17)(18)(19)(20)(21). In the present case, M-NBI was able to diagnose cancer in part of the large, elevated lesion, and we were able to perform a target biopsy.…”
Section: Discussionmentioning
confidence: 53%
“…However, it is very difficult to accurately diagnose cancerous lesions among the numerous polyps present in cases of GJP coexisting with gastric cancer. Indeed, no case study has yet reported an accurate initial diagnosis of coexisting GJP and cancerous lesions with M-NBI and a target biopsy (Table) (15)(16)(17)(18)(19)(20)(21). In the present case, M-NBI was able to diagnose cancer in part of the large, elevated lesion, and we were able to perform a target biopsy.…”
Section: Discussionmentioning
confidence: 53%
“…Some studies have reported an association between the germline variants of SMAD4 and the frequency of gastric lesions and HHT [30,31]. In a study of immunostaining for SMAD4 in gastric lesions of JPS, SMAD4 expression disappeared in 70%-80% of cases, suggesting that SMAD4 immunostaining may be effective as a screening test [32,33]. Patients with SMAD4 pathogenic variants have also been reported to have various complications such as pulmonary arteriovenous malformation, aortic arch dilatation, protein-losing enteropathy, and immunodeficiency [34][35][36].…”
Section: Explanationmentioning
confidence: 99%
“…Several cases have reported that the histological findings of intervening mucosa in gastric JPS show inflammatory changes that are sometimes similar to those of polyp lesions, as in the present case. 2,5 Therefore, the description of intervening mucosa in the Japanese diagnostic criteria for JPS is not always applicable to gastric JPS. In such cases, germline genetic testing and SMAD4 immunostaining can be useful to differentiate JPS from CCS.…”
Section: Germline Genetic Testing Of Blood (National Cancermentioning
confidence: 99%
“…4 Therefore, it is believed that JPS and CCS can be distinguished by histological findings of the intervening mucosa. 2 Herein, we report a case of massive gastric JPS, in which abnormal findings of the intervening mucosa and lack of family history made the diagnosis difficult.…”
mentioning
confidence: 97%
See 1 more Smart Citation